Wives with long and high-quality hair have more frequent sex - Cheon, Jeong Eun; Kim, Jeongwoo John; Kim, Young-Hoon (Frontiers in Psychology, 2024)
The image of an ideal woman often involves her having long, silky hair. However, the dearth of psychological research on hair limits the understanding on how women's hair functions in romantic relationships. While some scholars have found that the appearance of women's hair signals reproductive potential to men, whether women's hair may affect their sexual lives remains unknown. To investigate the function of hair in romantic relationships, we tested whether women's hair quality and length are associated with sexual frequency in marital dyads. We conducted a paid online survey involving 204 marital dyads. The results indicated that women with long and high-quality hair experienced more frequent sexual intercourse with their spouse, as it heightened their husband's perception of their attractiveness and, consequently, intensified their husband's sexual desire towards them. Neither men's hair length nor quality was associated with sexual frequency. Implications of the study are further discussed.